2011
DOI: 10.1371/journal.pone.0026242
|View full text |Cite
|
Sign up to set email alerts
|

Ectodermal Influx and Cell Hypertrophy Provide Early Growth for All Murine Mammary Rudiments, and Are Differentially Regulated among Them by Gli3

Abstract: Mammary gland development starts in utero with one or several pairs of mammary rudiments (MRs) budding from the surface ectodermal component of the mammalian embryonic skin. Mice develop five pairs, numbered MR1 to MR5 from pectoral to inguinal position. We have previously shown that Gli3Xt-J/Xt-J mutant embryos, which lack the transcription factor Gli3, do not form MR3 and MR5. We show here that two days after the MRs emerge, Gli3Xt-J/Xt-J MR1 is 20% smaller, and Gli3Xt-J/Xt-J MR2 and MR4 are 50% smaller than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…Deletion of Gli3 causes inappropriate encroachment of hair follicles close to MR2, which itself protrudes abnormally from Gli3 mutant ectoderm, similar to cervical mammary placodes in W6cre/CAGC8 mutants. Interestingly, deletion of Gli3 also prevents the normal regression of mammary buds in male mice, comparable to the persistence of male MRs within the anterior ectopic zone of W6cre/CAGC8 mice (Chandramouli et al, 2013;Hatsell and Cowin, 2006;Lee et al, 2011Lee et al, , 2013Ulloa et al, 2007).…”
Section: Ectodermal Tbx3 Ablation Abolishes Both Ectopic and Normal Mmentioning
confidence: 88%
See 1 more Smart Citation
“…Deletion of Gli3 causes inappropriate encroachment of hair follicles close to MR2, which itself protrudes abnormally from Gli3 mutant ectoderm, similar to cervical mammary placodes in W6cre/CAGC8 mutants. Interestingly, deletion of Gli3 also prevents the normal regression of mammary buds in male mice, comparable to the persistence of male MRs within the anterior ectopic zone of W6cre/CAGC8 mice (Chandramouli et al, 2013;Hatsell and Cowin, 2006;Lee et al, 2011Lee et al, , 2013Ulloa et al, 2007).…”
Section: Ectodermal Tbx3 Ablation Abolishes Both Ectopic and Normal Mmentioning
confidence: 88%
“…Ectopic mammary glands occur most commonly at inappropriate sites along these lines. Evidence in rabbits and mice suggests that mammary placodes form by migration of epithelial cells into and along the mammary lines, resulting in the five pairs of MRs developing non-sequentially at characteristic positions along the body axis (Lee et al, 2011;Propper, 1978). Molecular requirements differ among the pairs of mammary placodes, and differential gene expression profiles may underlie some of the heterogeneous attributes and susceptibilities to tumor incidence in adult mammary glands .…”
Section: Introductionmentioning
confidence: 99%
“…The molecular and cellular basis of this transition is still unclear. However, earlier morphological studies in rabbits and recent cell-tracing experiments in mice suggested that the formation and growth of mammary placodes involve migration and reassembly of the mammary epithelial cells (Propper, 1978;Lee et al, 2011). This dynamic mode of placode formation suggests that mammary glands may have adopted a distinct molecular mechanism for placode induction.…”
Section: Introductionmentioning
confidence: 99%
“…1B). The thickness and shape of the collected mesenchymal cups varied slightly, along with the variation in shape of the five mammary buds and their adjacent mammary mesenchyme (Lee et al, 2011), but was fairly consistent among replicates of the same bud.…”
Section: Rehydration and Precise Dissectionmentioning
confidence: 88%